Sleep Disorders in Psychiatric Patients A Practical Guide (Springer Berlin Heidelberg, 2018)
This book is designed to give clinicians a practical guide to the detection, assessment and treatment of sleep disorders in patients with psychiatric illness in order to better treat both their sleep disorder and their psychiatric disorder. In addition to providing a thorough introduction to the major sleep disorders, it offers clear guidance on how to assess and manage these disorders in patients with a wide range of psychiatric conditions. The role of psychiatric medication and special considerations to be borne in mind when treating psychiatric patients are also addressed. Although it is aimed primarily at psychiatrists, this will also be a useful handbook for sleep clinics and general practitioners who frequently have to manage patients with both psychiatric and sleep disorders. .